Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1016/s0925-4439(99)00089-7
|View full text |Cite
|
Sign up to set email alerts
|

Migration of CD18-deficient neutrophils in vitro: evidence for a CD18-independent pathway induced by IL-8

Abstract: Neutrophils isolated from a child with severe leukocyte adhesion deficiency 1 (LAD1) had a complete absence of expression of the CD11/CD18 beta2 integrin family of adhesion molecules, and were shown to be deficient in the in vitro adhesion and migration properties. However, we found that interleukin-8 (IL8), a potent chemoattractant for neutrophils, and sputum sol phase induced these LAD1 neutrophils to migrate through an endothelial cell layer in vitro, and confirmed that this migration was CD18-independent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The basis of the engagement of CD18-independent mechanisms is not clear. In an in vitro system in which CD18-indepenent pathways of transendothelial PMN migration were identified, IL-8 was shown to promote the CD18-independent emigration of PMN (8,24,26,39). In another study we showed that the E. coli induced the release of macrophage inflammatory protein-2 (our unpublished observation), the murine homologue of IL-8, in lung tissue, which could account for the observed CD18-independent tissue PMN sequestration and migration responses.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The basis of the engagement of CD18-independent mechanisms is not clear. In an in vitro system in which CD18-indepenent pathways of transendothelial PMN migration were identified, IL-8 was shown to promote the CD18-independent emigration of PMN (8,24,26,39). In another study we showed that the E. coli induced the release of macrophage inflammatory protein-2 (our unpublished observation), the murine homologue of IL-8, in lung tissue, which could account for the observed CD18-independent tissue PMN sequestration and migration responses.…”
Section: Discussionmentioning
confidence: 70%
“…Activation of PMN adherent to the microvessels plays a key role in the inflammatory response and contributes to the mechanism of microvascular injury by the release of oxidants, proteases, chemokines, and other mediators (3,(5)(6)(7)(8). Assessment of PMN adhesion has shown that CD11/CD18 integrin complexes expressed on PMN are essential for PMN adhesion to the vascular endothelium and migration of PMN across the endothelial barrier (9 -14).…”
mentioning
confidence: 99%
“…However, in light of new published data this distinction obviously oversimplifies this multiform process. Which of these both transmigration mechanisms are actually operative is also in part dependent on the chronicity of reactions as well as on the various chemotaxins (43,44). Thus, a CD18-independent transendothelial migration of PMN can be stimulated in vitro by the host-derived chemoattractants IL-8 and leukotriene B 4 (45).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies of neutrophil locomotion indicate that different chemotactic factors may select different pathways. For example, neutrophil emigration through human umbilical vein endothelial cell monolayers is not blocked by antibodies to ␤ 2 -integrins if the stimulus is IL-8 or leukotriene (LT) B 4 , but transendothelial migration in response to the chemotactic tripeptide [N-formyl-methionyl-leucyl-phenylalanine (fMLF)] is ␤ 2 -integrin dependent (179). Clear evidence for such chemotactic factor selection in vivo has not been published.…”
Section: Introductionmentioning
confidence: 99%